STRATEGIC MANAGEMENT IN LOCAL GOVERNMENT: A SYSTEMATIC LITERATURE REVIEW - Nuh, Mohammad; Pratama, M. Rizki (Jurnal Mediasosian : Jurnal Ilmu Sosial dan Administrasi Negara, 2025)
The shift in governance from a centralized to a decentralized system has made local governments increasingly significant in managing public affairs and delivering services to society. The high expectations of the public and changes in the global environment present unique challenges for local governments. Consequently, local governments are required to be more adaptive and innovative in their governance practices. In line with public sector management reforms, the last two decades have seen both practices and studies in public administration emphasizing the importance of adopting management tools or instruments known as public sector strategic management. This research seeks to explore the development of theories and concepts of strategic management as studied by researchers and published in internationally reputable databases. A systematic literature review method is applied to the theme of public sector strategic management in local government to examine the development of this theme over the past two decades. This research identifies gaps and highlights the evolving themes in strategic management, underscoring the need to integrate interdisciplinary methodologies and global perspectives. Future studies should prioritize leveraging digital tools, participatory frameworks, and equity-driven approaches to address rapidly changing governance demands.